The fantastic of dignified journey "The dignified journey in Al-tashwof ela rejal altasawof by Ibn Al-Zayyat Al-tdeli an example" - Kaddah, Roaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research is composed of two parts: The first is theoretical and applicational. The theoretical section clarified both The fantastic and dignified terms. It elaborates saying in "The fantastic of dignified journey" described fantastic especially for representing features of the fantastic. Moreover it adds to what corresponds to the dignity nature. On the other hand the applicational section analyses texts of the dignified journeies in altasawof. It also reveals several important results of this section like expanding time frequency of the dignified journey, the changeable criterion based in texts in judging texts according to the tribal receiver of dignity. Furthermore, there appeared a lot of topics like "subjects of I", with absence of "subjects of You" ones. Another thing resulted there the vanishing of literary mission in the condensed dignified journeies through news or a statement. At last, there appeared two new functions for fantastic teaching and cognitive, in addition to the main tasks of the fantastic: literary and the socialistic ones.